Photon-trapping array for enhanced midwave infrared photoresponse - Suo, Fei (2022)
Photonic structures have been attracting great attention as they have the ability to manipulate the photoresponse. Here, we report a hole array for effective photon trapping, therefore facilitating optoelectrical conversion of a midwave infrared photodetector. The integrated device consists of an InAsSb-based heterojunction photodiode and an embedded symmetric hole array penetrating through the top wide bandgap layers into the absorption region, which enables lower dark current, better broadband absorption, and improved polarization-independent photoresponse. The photoresponse enhancements of 26%–170% are achieved in the 2–5 µm range under zero power supply at temperatures from 293 K to 78 K. Combined with the effect of slightly decreasing in bulk dark current density, the zero-bias detectivity is increased by 29% at room temperature without sacrificing the response speed, where the enhanced detectivity increases to 2.09 × 109 Jones. This proposed approach provides a new strategy to boost optoelectrical conversion of photodetectors, thereby facilitating robust photodetection for widespread applications.